Do Changes in the Exchange Rate Have an Asymmetric Effect on the Trade Balance between Vietnam and Japan?. Issue 1 (2nd January 2022) - Nguyen, Quang Dong; Tran, Thi Ha; Nguyen, Quang Huy
Abstract : The paper examines the impact of changes in the exchange rate on Vietnam's trade balance with Japan based on the employment of both aggregate and industry-level data in a set of linear and nonlinear autoregressive distributed lag models. The results from the models indicate a degree of bias in regression when using aggregate data and a linear ARDL approach. Among the 19 industries under consideration, the NARDL model presents different responses to exchange rate movements from 16 industries, which account for 46% of imports and 63% of exports between Vietnam and Japan. Using aggregate data, the model shows that the exchange rate positively affects the Vietnam-Japan trade balance in the case of currency depreciation, whereas currency appreciation has no impact on the trade balance. Thus, it is concluded that the exchange rate is an effective tool to stimulate exports and improve the trade balance between Vietnam and Japan.